THE EFFECT OF ENGAGE, STUDY, ACTIVATE TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT - Rahmadayani Saragih; Masitowarni Siregar; Anni Holila Pulungan (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2015)
This study is aimed at finding out the effect of Engage, Study, Activate technique on students’ achievement in writing narrative text. This research applied experimental design. The instrument used to collect the data was a written test. The population was the 2015/2016 second year students (grade VIII) of SMP N 1 Sei Rampah. There were nine paralel classes that consisted of 30 students. The total number of the population were 270 students. The total number of the sample were 60 students. The researcher selected the sample by choosing only 2 classes  by using sampling technique. The sample was divided into two groups, experimental group and control group. The experimental group was taught by applying Engage, Study, Activate technique while the control group was taught without applying Engage, Study, Activate technique. The data were taken by administering the pre-test and post-test to both control and experimental groups. These data were analyzed by using t-test. The result of computing the t-test obviously showed that t-observed (4.383) is higher than t-table (1.671) with the degree of freedom (df= 58) at the level significance 0.05 one tail test. It means that alternative hypothesis stating that there is a significant effect of Engage, Study, Activate technique on students’ achievement in writing narrative text is accepted. Keywords : ESA Technique, Writing Narrative Text